Donald Trump's Foreign Policy: Withdrawal From International Regimes and Organizations - Maulana, Muhammad Alfian; Yuliantoro, Nur Rachmat (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2024)
This research delves into transformative shifts in United States (US) foreign policy during Donald Trump’s presidency, specifically focusing on withdrawals from crucial international agreements like the Paris Agreement, TPP, UNHRC, UNESCO, and UNRWA. Utilizing the Poliheuristic theory, the study aims to comprehend the rationale behind the US withdrawal from international regimes and organizations during Trump's administration. The research employs a dual-stage assessment within the Poliheuristic theory; the cognitive aspect, considering policymakers’ values, and the rational aspect, evaluating potential gains and losses. President Trump confronted three options for international organizations: remaining, renegotiating, or withdrawing. Qualitative techniques were incorporated to analyze the prioritization of the America First promise and assess the country’s engagement with these entities. Rejecting the option to remain led to a rational evaluation of renegotiation or exit. The decision to withdraw was strategically made to address unmet renegotiation demands, minimizing significant financial burdens for the US.